Future of forest energy in Europe in 2030 - Riala, Maria; Asikainen, Antti (Finnish Forest Research Institute, 2012)
The need to increase the use of forest energy is connected to the EU goals for use of renewable energy. If the targets are to be reached, forest energy should play a role. The share of forest energy out of all renewable energy will vary between countries. This study focuses on the future of forest energy. The method chosen was a two-round dissensus-based Delphi. The respondents consisted of members of the COST action FP 0902 and in the second round also of members of the RoK-FOR programme. Most of the respondents were experts in the field of forestry, from more than 20 countries. The first section of the survey addressed the issue of trends and operational environment. The respondents assessed the likelihood and desirability of several trends happening by 2030. They also, for example, estimated the increase in use of forest energy and the constraints to its use. There seemed to be a strong belief in technological development and beneficial policy interventions, but the respondents also recognised the problematic competitive situation in relation to other sources of energy. In terms of technological development, the experts saw that the main challenge to address is transport and logistics. This included a wide range of different issues, such as the handling of bulky, low-value product in an efficient way. The experts saw greatest development potential in improving energy density before transport, and multi-tree handling. Driver-assisting systems would be particularly useful in helping with the planning of felling, e.g. in the case of placing of tracks. Labour shortages are also a pertinent issue. The respondents gave many suggestions on ways to attract new workers to forestry, for example by increasing the salary to the level of manufacturing industry, and by promoting forestry as an environmentally friendly and technologically advanced employer. Overall, this report describes some alternative future prospects, which could be achieved by decisive action. Hopefully this report provides insights for bioenergy sector and policy-makers and offers pathways to increasing the use of forest energy in Europe to the target level.
Keywords: Delfi; haasteet; metsäenergia; teknologia; trendit; tulevaisuuden tutkimus; työvoima; forest energy; futures research; labour; technological development; trends